2008
DOI: 10.1523/jneurosci.1670-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Axonal Elongation and Pathfinding from the Entorhinal Cortex to the Dentate Gyrus in the Hippocampus by the Chemokine Stromal Cell-Derived Factor 1α

Abstract: During the early developmental stage, a neural circuit is established between the entorhinal cortex (EC) and the hippocampal dentate gyrus (DG) via the perforant pathway. However, the manner in which the perforant fibers are navigated has mostly remained a mystery. Here, we analyzed the functional role of a chemokine, namely, stromal cell-derived factor 1␣ (SDF-1␣), in the navigation of the perforant fibers. SDF-1␣ was observed to promote neurite growth, which is dependent on mDia1, in cultured entorhinal cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…53,54 Apart from its migratory function, SDF-1 has also been shown to be engaged in neuromodulation 17,55 and axonal elongation from the entorhinal cortex towards the dentate gyrus. 56 There is a species-specific predominance of particular splicing variants in the brain. In mice SDF-1β is the most abundant isoform, while in rats, it is SDF-1γ.…”
Section: Pathology-specific Rolementioning
confidence: 99%
“…53,54 Apart from its migratory function, SDF-1 has also been shown to be engaged in neuromodulation 17,55 and axonal elongation from the entorhinal cortex towards the dentate gyrus. 56 There is a species-specific predominance of particular splicing variants in the brain. In mice SDF-1β is the most abundant isoform, while in rats, it is SDF-1γ.…”
Section: Pathology-specific Rolementioning
confidence: 99%
“…Previous reports have shown that RGMa inhibits mammalian CNS neurite outgrowth in vitro (Brinks et al, 2004;Hata et al, 2006;Kubo et al, 2008;Ohshima et al, 2008;Yoshida et al, 2008). To evaluate the involvement of p120GAP in the long-term effects of RGMa, we performed two types of in vitro neurite outgrowth assays.…”
Section: The Involvement Of P120gap In Rgma-induced Neurite Outgrowthmentioning
confidence: 99%
“…It has been demonstrated that RGMa is expressed in the inner molecular layer of the hippocampal dentate gyrus and that it restricts the axonal extension of developmental entorhinal cortical neurons, thereby facilitating appropriate connection with the dentate gyrus (Brinks et al, 2004;Ohshima et al, 2008). Furthermore, a recent study reported that RGMa suppresses neurite outgrowth, branching, and synapse formation in cultured cortical neurons (Yoshida et al, 2008), suggesting that RGMa may contribute to the formation of a precise wiring pattern, such as the entorhino-hippocampal connection, by inhibiting both synapse formation in the inner molecular layer of the dentate gyrus and axonal extension of the entorhinal cortical neurons.…”
Section: Roles Of the Rgma-mediated Ras Inactivation In Neuronal Netwmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Li et al [56] found that the final settlement of the DG granule precursor cells at the subgranular zone is not dependent on the SDF-1α/CXCR4 signaling. In addition, SDF-1α guides the growth of perforant fibers linking the entorhinal cortex with the DG in a neural circuit [58]. During the early postnatal period, SDF-1α is expressed in Cajal-Retzius cells on the upper and lower blades of the dentate and in the maturing dentate granule neurons, as well as in the meninges [59].…”
Section: Roles Of Sdf-1α/cxcr4 In Brain Developmentmentioning
confidence: 99%